IMPLEMENTATION OF STRATEGIC PLAN FOR POLEWALI DISTRICT GENERAL HOSPITAL IN POLEWALI MANDAR REGENCY - Juharni, Juharni (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
The goal to be achieved is to ensure that the Strategic Plan of Polewali District General Hospital, Polewali Mandar Regency, is well-directed and serves as a guideline in the preparation of the Annual Budget Plan. It aims to enhance human resources ready to serve in accordance with the Vision and Mission of Polewali District General Hospital, as well as to improve the welfare of actively contributing employees. The research method employed in this study is qualitative research using a descriptive approach. Data were obtained through instruments consisting of surveys, observations, focus group discussions, and in-depth interviews. Data were also acquired through documents from Polewali District General Hospital. The research findings indicate that (1) the performance of the hospital can be well-directed by improving service quality to the community according to 4 (four) perspective variables: financial perspective, customer perspective, internal business perspective, and growth and learning perspective, and (2) To enhance the effectiveness of hospital services, it is important to identify opportunities and threats, strengths, and weaknesses based on the analysis of the situation regarding three perspective variables.